1996
DOI: 10.1097/00005373-199611000-00004
|View full text |Cite
|
Sign up to set email alerts
|

After the Shooting Stops

Abstract: Despite a well-functioning trauma system that maximized survival from devastating injury, considerable long-term morbidity and disability persists. Efforts at prevention of mass casualties seem to be the only potential solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Firearm injury has a high risk of re-hospitalizations especially in patients with greater severity, which increases their likelihood of rehospitalizations. 36 A second limitation is the lack of detailed integrated information regarding emergency department visits, where they were treated and released without hospitalization. Of all the non-fatal firearm injuries, about 40% are treated and released in the emergency department, while the rest are hospitalized.…”
Section: Discussionmentioning
confidence: 99%
“…Firearm injury has a high risk of re-hospitalizations especially in patients with greater severity, which increases their likelihood of rehospitalizations. 36 A second limitation is the lack of detailed integrated information regarding emergency department visits, where they were treated and released without hospitalization. Of all the non-fatal firearm injuries, about 40% are treated and released in the emergency department, while the rest are hospitalized.…”
Section: Discussionmentioning
confidence: 99%
“…1 Besides high death toll firearm injuries cause significant morbidity, long-term physical and psychological disability for individuals, families, communities and societies. 2 In 1996, the World Health Assembly declared violence as a leading global public health problem high-lighting a need for implementing the global strategy to prevent it. 3 Firearms and their use are modifiable risk factors, 4 which if recognized and addressed, could help decrease the burden of violent deaths.…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-eight percent (13/34) of all studies reported vascular injuries [ 12 , 15 , 17 19 , 24 , 32 , 36 , 38 40 , 42 ]. Patients with reported vascular injuries after CPMSs ranged from 8 to 29% (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Patients with reported vascular injuries after CPMSs ranged from 8 to 29% (Table 3 ). Vascular procedures, in general, included direct arterial and/or venous repair [ 15 , 21 ]. There was no specific data on more advanced vascular reconstructions [ 15 , 19 , 21 , 32 , 39 ].…”
Section: Resultsmentioning
confidence: 99%